Current status of epilepsy treatment and efficacy of standard phenobarbital therapy in rural areas of Northern China. (3rd August 2017) - Yu, Jinbei; Luo, Nan; Wang, Zan; Lin, Weihong
Abstract : Purpose: To investigate the current status of epilepsy treatment and the efficacy and adverse effects of phenobarbital therapy in rural areas of Northern China. Methods: A total of 2192 patients diagnosed with convulsive epilepsy were recruited from seven different rural regions in Jilin Province, China to investigate the current status of epilepsy treatment, and 1379 of them were enrolled in a standard phenobarbital therapy trial. Patients were selected according to strict inclusion and exclusion criteria, and medical records for all patients were collected and analyzed before the standard treatment was started. Patients were followed up monthly, and efficacy in 1218 patients was analyzed at 1, 3, 6 and 12 months of treatment. Results: More patients had the initial seizure in juveniles than in adults, and 40.72% of the 2192 patients were not receiving any treatment before the treatment trial. The efficacy of phenobarbital increased and adverse effects decreased within the treatment period. Among the 349 patients who were followed up for 12 months from the beginning of the phenobarbital treatment, seizures were decreased by more than 75% in 71.3% of patients using a low-to-medium dose of phenobarbital. Major adverse effects of phenobarbital included mild exhaustion, drowsiness, dizziness and headache. Conclusions: Standardized long-term and regular administration of phenobarbital at a low-to-medium dose can be used as an effective, economic and safe treatment against epilepsy in rural areas.